2015
DOI: 10.1093/jnci/djv219
|View full text |Cite
|
Sign up to set email alerts
|

Height and Breast Cancer Risk: Evidence From Prospective Studies and Mendelian Randomization

Abstract: Our study provides strong evidence that adult height is a risk factor for breast cancer in women and certain genetic factors and biological pathways affecting adult height have an important role in the etiology of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
81
2
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 72 publications
16
81
2
7
Order By: Relevance
“…Our finding confirms and extends the results from observational studies that have shown that taller height is associated with improved cognitive performance [68], lower rates of death from dementia [9], and reduced risk of AD [10]. The association between genetically predicted height and AD is in the same direction as the genetic association between height and risk of cardiovascular disease [12, 13] but opposed the direction for certain cancers [1416]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our finding confirms and extends the results from observational studies that have shown that taller height is associated with improved cognitive performance [68], lower rates of death from dementia [9], and reduced risk of AD [10]. The association between genetically predicted height and AD is in the same direction as the genetic association between height and risk of cardiovascular disease [12, 13] but opposed the direction for certain cancers [1416]. …”
Section: Discussionsupporting
confidence: 87%
“…This genetic approach has been utilized to explore the association between adult height and risk of cardiovascular disease [12, 13] and cancer [1416], but has not yet been used to investigate the association between height and AD. The aim of this study was to examine whether genetically predicted height is associated with AD.…”
Section: Introductionmentioning
confidence: 99%
“… a Summary sample sizes of studies included in the GAME-ON consortium. b The total number of SNPs used to construct the instrumental variable. c OR and RR represent the risk associated with a 10-cm increase in adult height. d Meta-analysis summary OR and 95% CI previously reported [53]. …”
Section: Resultsmentioning
confidence: 99%
“…The authors do not draw conclusions regarding the association of height with breast cancer risk according to ER/PR status. Instead, they conclude that their results demonstrate that height is causally implicated in breast cancer etiology and that height and breast cancer share genetic risk variants (33). …”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 159 prospective cohorts that included 5,216,302 women and 9,732 breast cancer cases with known ER status, found a positive association between height and risk of ER+ tumors (HR: 1.18, 95% CI: 1.13-1.23 per 10cm increase), but no association with ER− tumors (HR: 1.00, 95% CI: 0.86-1.14). Interestingly, when tumors were classified jointly by ER and progesterone receptor (PR) status, there was a borderline significant association with ER−/PR− tumors (HR: 1.08, 95% CI: 0.99-1.18) (33). They also conducted a Mendelian randomization analysis using a genetic risk score derived from 168 height-associated variants and found strong positive associations with ER+ and ER+/PR+ tumors and no association with ER− or ER−/PR− tumors.…”
Section: Discussionmentioning
confidence: 99%